A hybrid blockchain method in internet of things for privacy and security in unmanned aerial vehicles network. (April 2022) - Abualsauod, Emad H.
Highlights: Identifying solutions towards challenges with overall security and privacy of UAV frameworks. Blockchain role in preserving and monitoring product quality in industrial chains. Blockchain providing information security and raising the quality level of security. Hybrid blockchain-based solution to provide an optimized solution for security and reliability in UAV-enabled IoT applications. Abstract: Unmanned Aerial Vehicles (UAVs) offer a huge amount of potential in a variety of applications, including healthcare, medical, traffic monitoring, military, and industry. UAVs are deployed in association with the Internet of Things (IoT) to facilitate receivers or end-users at the end for delivering IoT services, resulting in a new research domain. The objectives of this research work are to analyze and classify the peer-reviewed research on UAV IoT frameworks and identify the solution towards challenges related to the overall security including the privacy of the frameworks. In the article, an optimum solution for various security and reliability challenges in UAV-enabled IoT applications is given using a fusion of several methods combining blockchain-based technologies. The results are obtained and compared on different parameters like overall system utility, accuracy, latency, and processing time. The proposed methodology results highlight the improvement and give novel directions toward future work. Graphical abstract: ML embedded blockchain structure for UAV. Image, graphical abstract